Non-volatile compact optical phase shifter based on Ge₂Sb₂Te₅ operating at 2.3 μm - Miyatake, Yuto (2023)
We investigate an optical phase shifter based on Ge2Sb2Te5 (GST) integrated with a Si waveguide at mid-infrared (MIR) wavelengths. Since the optical absorption of both amorphous and crystalline GST can be reduced at a longer wavelength, we demonstrate that the optical loss of the phase shifter can be reduced at MIR wavelengths. The measured optical loss per π phase shift of a phase-change material (PCM) phase shifter at 2.32 µm wavelength is 2.6 dB/π, which is more than 80 times smaller than that at 1.55 µm wavelength (21.7 dB/π) and more than 5 times smaller than that at 1.92 µm wavelength (9.7 dB/π). Moreover, resonance wavelength tuning of an add-drop micro-ring resonator using a PCM phase shifter at 2.32 µm wavelength is demonstrated owing to the low-loss optical phase shift. These findings reinforce the applicability of the approach toward a low-loss optical phase shifter based on PCMs operating at MIR wavelengths on a Si photonic platform for quantum computing, sensing, and optical communication.